PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SEPATU NIKE BAGI GEN Z DI SURABAYA - Adji Setya Wardana; Hery Pudjoprastyono; Virginia Mandasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to examine and analyze the influence of Celebrity Endorser and Brand Image on the purchase decision of Nike shoes among Gen Z in Surabaya. The population for this study consists of individuals who have purchased Nike shoes, with a sample size of 130 respondents. Data analysis was conducted using the Partial Least Squares (PLS) method. The results of the data analysis and previous discussions regarding the impact of Celebrity Endorser and Brand Image on the purchase decision of Nike shoes among Gen Z in Surabaya are as follows: Celebrity Endorser has a positive contribution to the purchase decision, meaning that the better the Celebrity Endorser, the better the purchase decision, and vice versa. Brand Image also contributes to the purchase decision, meaning that the better the brand image, the better the purchase decision, and vice versa.